Unlocking the Potential: Increasing Muscle Strength in Lower Limbs of Youth Soccer Players over Five Weeks through Mat Pilates Training—A Pilot Study - Franciele Parolini; Gladson Bertolini; Rubim Santos; Manoela Abreu; Ana Laura Nogueira; Dernival Bertoncello (Sensors, 2024)
The interest in soccer generally starts during childhood, with children and young people often looking for opportunities in sports. New exercise techniques can be effective in improving training. The aim of this study was to compare the effects on the strength and physical posture of a group practicing Pilates with another not practicing Pilates, both undergoing continuous football training. In this controlled randomized clinical trial, the participants were 15 soccer club members, who had a training frequency of least three times weekly. The sample was divided into a control group (n = 7) of players who did not undergo any therapeutic intervention (only the usual training) and a Pilates group (n = 8) of players who participated in the mat Pilates program. The intervention consisted of fifteen sessions. Postural evaluations were performed using biophotogrammetry and force analysis. Significant improvements were obtained in terms of increased muscle strength (p = 0.001) for the Pilates group, but there were no significant postural alterations when comparing the two groups. Five weeks of mat Pilates was sufficient to increase lower limb muscle strength in young football players. This pilot study indicates that Mat Pilates as a method that could be planned to be included in training.